Analysis of Plant Growth and Gallic Acid Content for Cavendish Banana (Musa acuminata) Shoot Culture with Bubble Column Bioreactor - Nunung Nurhayati; Rizkita Rachmi Esyanti; Khalilan Lambangsari (Journal of Integrated and Advanced Engineering (JIAE), 2022)
Cavendish banana (Musa acuminata) is one of the most important fruits in the world. Cavendish shoots tissue culture using bubble column bioreactor can be a solution to produce high yielding plantlet and gallic acid due to the aeration with minimum shear stress. In this study, the average growth rate, presence of gallic acid, and antioxidant activity (IC50) in the bubble column bioreactor (200 mL capacity) with the aeration rates of 1 mL/s and 2 mL/s using Murashige & Skoog half-strength liquid medium supplemented with 0.5 ppm gibberellic acid will be analyzed. The aeration system used was atmospheric air. The leaves and stems were extracted by maceration using 96% ethanol solvent (1:10 (w/v)). A qualitative phenolic test with FeCl3, thin layer chromatography, and antioxidant test with 2,2-diphenyl-1-picrylhydrazyl was carried out. The average growth rate in the bioreactor were 0.22 ± 0.001 g/day (1 mL/s) and 0.21 ± 0.001 g/day (2 mL/s). All the leaf and stem extracts showed positive results for the phenolic test, but the presence of gallic acid could not be detected clearly by thin-layer chromatography. The IC50 values in aeration rates of 1 mL/s and 2 mL/s of the leaves were 41.35 and 79.54 μg/mL, respectively, while the stems were 51.87 and 104.94 μg/mL, respectively. It could be concluded that the growth of the banana plantlet and the production of antioxidants in the bubble column bioreactor was higher in aeration rate of 1 mL/s than 2 mL/s.